2019
DOI: 10.1080/15384047.2019.1685157
|View full text |Cite
|
Sign up to set email alerts
|

CXCR4/TGF-β1 mediated hepatic stellate cells differentiation into carcinoma-associated fibroblasts and promoted liver metastasis of colon cancer

Abstract: Background: Liver metastasis of colon cancer is strongly affected by the tumor microenvironment (TME), with interactions between tumor cells and cancer-associated fibroblasts (CAFs) in particular. TGFβ is well known for its ability to mediate the CAF phenotype, and CXCR4 expression is closely correlated to poor prognosis in CRC. The relationship between these two signaling pathways remains to be delineated in liver metastasis of colon cancer. Methods: Immunohistochemistry was employed to investigate CXCR4 expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 38 publications
(50 reference statements)
3
58
0
Order By: Relevance
“…28,29,48,49 Through tumor-stroma crosstalk, tumor cells are able to recruit and activate surrounding liver microenvironmental cells into myofibroblasts. 10,28,32,48,50,51 TGF-β signaling is key in this crosstalk. Activation of HSCs into aHSCs leads to secretion of cytokines, including platelet derived growth factor (PDGF), HGF, TGF-β, stromal derived factor (SDF), ECM proteins fibronectin and collagen, and matrix metalloproteases (MMPs).…”
Section: Steps 4-6: Adaptation To Local Niche Leads To Micrometastasimentioning
confidence: 99%
See 2 more Smart Citations
“…28,29,48,49 Through tumor-stroma crosstalk, tumor cells are able to recruit and activate surrounding liver microenvironmental cells into myofibroblasts. 10,28,32,48,50,51 TGF-β signaling is key in this crosstalk. Activation of HSCs into aHSCs leads to secretion of cytokines, including platelet derived growth factor (PDGF), HGF, TGF-β, stromal derived factor (SDF), ECM proteins fibronectin and collagen, and matrix metalloproteases (MMPs).…”
Section: Steps 4-6: Adaptation To Local Niche Leads To Micrometastasimentioning
confidence: 99%
“…In the liver, various cell types are a source of TGF-β, including tumor cells, myofibroblasts, and local immune cells. 14,50,60,90 Below, we will describe the current knowledge of TGF-β during the different phases of hepatic colonization. A schematic overview of different functions of TGF-β during liver metastasis is shown in Figure 3.…”
Section: Tgf-β In Liver Metastasismentioning
confidence: 99%
See 1 more Smart Citation
“…Tan et al . previously reported that human HSC cell line LX2 could be converted into α-SMA(+)/FSP1(+) CAFs with exposure to tumor-derived TGF-β in vitro [ 38 ]. A recent transgenic model also suggested that the hepatocyte-derived platelet derive growth factor-C (PDGF-C) transformed HSCs into myofibroblast-like cells, which in turn produced cytokines to promote the development of HCC [ 39 ].…”
Section: Cafs In Hccmentioning
confidence: 99%
“…Unsurprisingly, HSCs are also present within CRC liver metastatic nodules, with the activated myofibroblast phenotype also associated with a metastasis-supportive niche [186,187]. Other resident cells within the hepatic microenvironment provide a source of pro-fibrogenic cytokines, in particular TGF-β, VEGF, PDGF and connective tissue growth factor (CTGF) [46], and activation of HSCs can also be directly induced by CRC cells [188]. Secretion of ECM remodeling factors from myofibroblasts such as matrix metalloproteinases (MMPs) generates a reactive stroma, permissive to tumor cell seeding and proliferation and suitable for neovascularization and angiogenesis [153,189].…”
Section: Inflammation In the Extravascular Phase Of Crc Liver Metastasismentioning
confidence: 99%